1996
DOI: 10.1007/bf02254961
|View full text |Cite
|
Sign up to set email alerts
|

How do Alliaceae stabilize their chromosome ends in the absence of TTTAGGG sequences?

Abstract: The Arabidopsis-type telomeric repeats (5'-TTTAGGG-3) are highly conserved. In most families of different plant phyla they represent the basic sequence of telomeres that stabilize and protect the chromosome termini. The results presented here show that Alliaceae and some related liliaceous species have no tandemly repeated TTTAGGG sequences. Instead, their chromosomes reveal highly repetitive satellite and/or rDNA sequences at the very ends. These apparently substitute the original plant telomeric sequences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 25 publications
(40 reference statements)
3
95
1
1
Order By: Relevance
“…The signals detected in the micronuclei are associated with the ends of chromosomes, since some studies conducted using the FISH technique showed that the rDNA sequences in A. cepa are located right in these chromosome regions [75,76]. Additionally, some studies that applied FISH in A. cepa showed that rDNA loci are present on the satellite chromosome 6 and the smallest chromosome 8 of this species [77].…”
Section: Fish (Fluorescent In Situ Hybridization)mentioning
confidence: 98%
“…The signals detected in the micronuclei are associated with the ends of chromosomes, since some studies conducted using the FISH technique showed that the rDNA sequences in A. cepa are located right in these chromosome regions [75,76]. Additionally, some studies that applied FISH in A. cepa showed that rDNA loci are present on the satellite chromosome 6 and the smallest chromosome 8 of this species [77].…”
Section: Fish (Fluorescent In Situ Hybridization)mentioning
confidence: 98%
“…In plants, the telomere repeat (TTTAGGG) n was isolated in Arabidopsis Ausubel 1988, Richards et al 1992), and this Arabidopsis-type repeat has been reported in many angiosperms and gymnosperms (Ganal et al 1991, Broun et al 1992, Cox et al 1993, Biessmann and Mason 1994, Fuchs et al 1995, Wellinger and Sen 1997, Hizume et al 1998. Allium cepa and A. fistulosum possess unique terminal repetitive sequences and/or rDNA sequences in place of the typical telomere sequence (Pich et al 1996, Pich andSchubert 1998), and the absence of Arabidopsis-type telomere repeats were reported in other Asparagales (Adams et al 2000(Adams et al , 2001. Weiss and Scherthan (2002) reported human-type telomere repeats instead of Arabidopsistype telomere repeats in Aloe chromosomes, while Sykorova et al (2003) described the coexistence of Arabidopsis-type and human-type telomere repeats on chromosomes in some plant species.…”
mentioning
confidence: 99%
“…Telomeres of A. cepa www.intechopen.com consist of two tandemly organized repeats -a 375-bp satellite sequence and rDNA repeats (Barnes et al, 1985;Pich et al, 1996;Pich & Schubert, 1998). Besides this, the telomeres in A. cepa are enriched with En/Spm transposable element-like sequence and Ty1-copia-like retrotransposons.…”
Section: The Onion Familymentioning
confidence: 99%